The Influence of Local Own- Source Revenue and Unemployment On Labor Force Through Human Development Index (HDI) - Aini, Lathifah; Runi, Naila Ananda; Nasution, Putri Andini; Salsabila, Salsabila; Silaban, Putri Sari Margaret Julianty (Jurnal Ekonomi Balance, 2025)
This study examines the influence of Local Own-Source Revenue and unemployment on the labor force participation rate in the regions of Java and Bali, with the Human Development Index (HDI) acting as a mediating variable. Using path analysis and EViews software, the research investigates both direct and indirect effects within a structural model. The results show that Local Own-Source Revenue has no significant direct effect on the labor force (p = 0.9100; direct effect = 0.004), and its indirect effect through HDI is also negligible. Similarly, unemployment does not have a statistically significant effect on labor force participation (p = 0.0966; direct effect = –0.205), nor does it show a significant indirect effect via HDI. These findings indicate that HDI does not mediate the relationship between Local Own-Source Revenue or unemployment and labor force participation in these regions. While HDI is widely regarded as a benchmark for human development, this study suggests it may not sufficiently explain labor force dynamics in the context of Java and Bali. Alternative factors such as the quality of education, economic diversification, urbanization, industrial structures, and access to digital infrastructure may have greater explanatory power. Future research is recommended to explore additional mediating variables and employ more detailed regional or sectoral analyses. Moreover, incorporating qualitative methods may help capture social and cultural dimensions that influence labor force behavior, thus offering a more comprehensive basis for policymaking.